2022
DOI: 10.1200/go.21.00395
|View full text |Cite
|
Sign up to set email alerts
|

Toward Equitable Access to Tertiary Cancer Care in Rwanda: A Geospatial Analysis

Abstract: PURPOSE Geographic access to care is an important measure of health equity. In this study, we describe geographic access to cancer care centers (CCCs) in Rwanda with the current facilities providing care and examine how access could change with expanded care infrastructure. METHODS Health facilities included are public hospitals administered by the Rwanda Ministry of Health. The WorldPop Project was used to estimate population distribution, and OpenStreetMap was used to determine travel routes. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Some of the environmental factors that may influence these differences include access to healthcare, air pollution, lifestyle, and socioeconomics. Studies suggest that differences in access to healthcare and diet may affect health outcomes between urban and rural areas [22,23,[35][36][37]. In addition, studies highlight the impact of air pollution on public health in urban areas [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the environmental factors that may influence these differences include access to healthcare, air pollution, lifestyle, and socioeconomics. Studies suggest that differences in access to healthcare and diet may affect health outcomes between urban and rural areas [22,23,[35][36][37]. In addition, studies highlight the impact of air pollution on public health in urban areas [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the environmental factors that may influence these differences include access to healthcare, air pollution, lifestyle, and socio-economics. Studies suggest that differences in access to healthcare and diet may affect health outcomes between urban and rural areas Smith et al, 2019;Fadelu et al, 2022;Samosir, Radjiman & Aninditya, 2023;Kalinda, 2023). In addition, studies highlight the impact of air pollution on public health in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Fadelu et al showed that 13%, 41%, and 85% of Rwandans can access cancer centers within 1, 2, and 4 hours of travel, respectively. 15 The same study also shows that some provinces in Rwanda have no access to cancer centers, hence patients have to travel long distances to other get diagnosed and treated for cancer in other provinces.…”
Section: Introductionmentioning
confidence: 89%